1982
DOI: 10.1002/jcp.1041100209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inhibitors of ornithine and S‐adenosylmethionine decarboxylases on L6 myoblast proliferation

Abstract: The role of polyamines in myoblast proliferation was studied by treating cells of Yaffe's L6 line of rat myoblasts with inhibitors of polyamine synthesis. Both an irreversible inhibitor of ornithine decarboxylase--difluoromethyl-ornithine (DFMO)--and a competitive inhibitor of S-adenosyl-methionine decarboxylase--methylglyoxal-bis(guanylhydrazone) (MGBG)--depressed spermidine levels and inhibited myoblast proliferation. Spermine levels were not significantly depressed by either inhibitor and putrescine levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In addition, the cell density of DFMO-treated cultures was essentially the same as that of control cultures (Table 1). These observations are consistent with the results obtained with a closely related subclone (L6-C5) which demonstrated that at least 48 hours of exposure to DFMO is needed before inhibition of cell proliferation becomes manifest (Stoscheck et al, 1982). Therefore, the protocol used in the experiments presented here precludes a n antiproliferative effect of DFMO; thus, the observed antidifferentiative effect of the drug is not secondary to an effect on cell density.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In addition, the cell density of DFMO-treated cultures was essentially the same as that of control cultures (Table 1). These observations are consistent with the results obtained with a closely related subclone (L6-C5) which demonstrated that at least 48 hours of exposure to DFMO is needed before inhibition of cell proliferation becomes manifest (Stoscheck et al, 1982). Therefore, the protocol used in the experiments presented here precludes a n antiproliferative effect of DFMO; thus, the observed antidifferentiative effect of the drug is not secondary to an effect on cell density.…”
Section: Discussionsupporting
confidence: 94%
“…All three polyamines, including spermine (the levels of which were not decreased by DFMO), prevented the inhibitory effect of DFMO on L6 myoblast differentiation. Previous work has shown that L6 myoblasts are capable of converting spermidine into putrescine (Stoscheck et al, 1982) and contain spermidineispermine-N1acetyltransferase activity (Erwin and Pegg, unpublished observations). This enzyme acetylates the aminopropyl end of either polyamine (Matsui et al, 1981).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This conclusion has been reached through experiments carried out with polyamine-auxotrophic mutants of bacteria (Algranati and Goldemberg, 1977;Abraham and Pihl, 1981) as well as with mammalian cells treated with specific inhibitors which block polyamine biosynthesis (Heby and Janne, 1981). However, some results suggest that the role of polyamines in cell growth is still unclear (Pardee et al, 1978;Stoscheck et al, 1982).…”
mentioning
confidence: 99%